2021
DOI: 10.3390/molecules26092612
|View full text |Cite
|
Sign up to set email alerts
|

A Novel N-Tert-Butyl Derivatives of Pseudothiohydantoin as Potential Target in Anti-Cancer Therapy

Abstract: Tumors are currently more and more common all over the world; hence, attempts are being made to explain the biochemical processes underlying their development. The search for new therapeutic pathways, with particular emphasis on enzymatic activity and its modulation regulating the level of glucocorticosteroids, may contribute to the development and implementation of new therapeutic options in the treatment process. Our research focuses on understanding the role of 11β-HSD1 and 11β-HSD2 as factors involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The change of the reaction conditions allowed obtaining compounds 3e-3f with isolated yields of 15.8-18.7%. Our previous research on the synthesis of 2-aminothiazol-4(5H)-one derivatives containing the spiro thiazole and alicyclic ring system showed that compounds of that type could be obtained by prolonged heating of the reactants in ethanol in the presence of N,N-diisopropylethylamine [30][31][32][33]. After 7 days for 3j and 14 days for 3i, a complete conversion of substrate to product was observed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The change of the reaction conditions allowed obtaining compounds 3e-3f with isolated yields of 15.8-18.7%. Our previous research on the synthesis of 2-aminothiazol-4(5H)-one derivatives containing the spiro thiazole and alicyclic ring system showed that compounds of that type could be obtained by prolonged heating of the reactants in ethanol in the presence of N,N-diisopropylethylamine [30][31][32][33]. After 7 days for 3j and 14 days for 3i, a complete conversion of substrate to product was observed.…”
Section: Resultsmentioning
confidence: 99%
“…High percent inhibition (76.40-69.22%) was also shown by derivatives containing isopropyl (3e), propyl (3d), and ethyl (3c) substituents, for which IC 50 was 1.19, 3.23, and 5.44 µM, respectively. On the basis of the obtained results, it can be concluded that in comparison with the derivatives containing chain substituents at the nitrogen atom [30][31][32][33], 2-(adamantan-1-ylamino)thiazol-4 (5H)-ones show a higher activity towards the inhibition of 11β-HSD1. In vitro studies showed that all the derivatives obtained also inhibit the activity of enzyme isoform 2, yet to a lesser extent (all analyzed compounds inhibited the activity of 11β-HSD2 by less than 50%).…”
Section: In Vitro Studiesmentioning
confidence: 89%
See 3 more Smart Citations